Загальномовне, регіональне та індивідуальне у зверненому мовленні новел Василя Стефаника - Скаб, Мар’ян (Kraków: Wydawnictwo «Scriptum», 2022)
NATIONAL, REGIONAL AND INDIVIDUAL IN THE ADDRESSED SPEECH OF VASYL STEFANYK’S NOVELS Summary Analyzing address expressions in Vasyl Stefanyk’s novels, the author draws conclusions, firstly, about the writer’s adherence to the national Ukrainian traditions of the language usage, secondly, about the writer’s use of the linguistic units and constructions widespread in Pokut’t’a, thirdly, about the significant peculiarities of the writer’s idiomatic style, caused by the specifics of the author’s life, the place where the plots of his works unfold, socio-political and aesthetic guidelines of the author. The received results are important and significant from the point of view of the complex systematic and dynamic description of the Ukrainian addressed speech
Keywords: adressed speech, Vasyl Stefanyk